Using a Realist Informed Qualitative Approach to Elaborate Programme Theory: Experiences From the Feasibility Phase of the D-PACT Project - Sarah Griffiths; Hannah Wheat; Sarah Morgan-Trimmer; Lauren Weston; Alex Gude; Tomasina M. Oh; Rod Sheaff; Richard Byng (International Journal of Qualitative Methods)
Realist approaches to complex health care evaluations are increasingly used and recommended in national evaluation guidelines. However, there remains a paucity of researcher guidance on methods for elaborating and refining programme theories throughout the stages of a realist evaluation project—from prospective theory development to feasibility work, to full evaluation. We present a step by step worked example of a realist approach to elaborating a programme theory for a health care intervention during the feasibility phase of the Dementia PersonAlised care Team. We explain how multiple qualitative methods can be applied to elaborate initial theory, supporting a shift away from a hypothetical explanation, towards a theory of how the model works in practice. We reflect on what worked well, and problems encountered, attending to both processes and the impact of working. Details are provided on how this approach can help enhance the likelihood of the intervention working in practice—through the application of new insights to interventionists’ training resources. We argue that coding to a framework constructed of ’If-Then’ initial programme theory statements enabled researchers to develop a realist analytic mindset and elaborated programme theory, ready for a fuller evaluation of the D-PACT intervention.